A review and SWOT analysis of aquaculture development in Indonesia - Michael A. Rimmer; Ketut Sugama; Diana Rakhmawati; Rokhmad Rofiq; Richard H. Habgood (Wiley Publishing Asia Pty Ltd, 2025)
Indonesia has a long history of aquaculture, dating from the 15th century. Subsequently, the country has become a significant contributor to global aquaculture production, destined for both international and domestic markets. In 2009 the Government of Indonesia announced its vision to see Indonesia become the highest (volume) producer of aquaculture products in the world by 2015, with production targets equivalent to an overall increase in production of 353% between 2009 and 2014. This paper comprises a PEEST (policy, economic, environmental, social, technical) review undertaken as a background study for a SWOT (strengths, weaknesses, opportunities, threats) analysis, the outcomes of the SWOT analysis and a discussion of possible approaches to support sustainable aquaculture development in Indonesia. To meet the vision of a dramatic expansion of aquaculture production, one or more of the following strategies is required: intensification and production segmentation, areal expansion, and/or production diversification. Most likely the continued development of aquaculture in Indonesia will be a combination of these three strategies, with the relative influence of each depending on production sector and market demands. A key issue identified in the PEEST review and SWOT analysis is the dominance (in terms of number) of Indonesian aquaculture by smallholder aquaculture farmers. We argue that a range of influences, including aquaculture production expansion and changing international market requirements, have the potential to negatively impact smallholder aquaculture farmers in Indonesia, and that further policy development should specifically address these issues.